Ilikita Purana Pura Braban Banjar Tanggayuda Bongkasa Village Badung Regency: Hindu Anthropological Study - Putu Eddy Purnomo Arta; Gede Bagus Wira Diputra (Journal of Pedagogi, 2026)
This article examines the Ilikita Purana of Pura Braban Banjar Tanggayuda, Bongkasa Village, as a religious and cultural document that records the history, structure, functions, and ritual system of the temple within Balinese Hindu society. The study aims to analyze the role of Pura Braban from historical, structural, and functional perspectives, as well as its significance within the framework of Hindu religious anthropology. The research employs a qualitative descriptive-analytical approach, using documentation studies, literature reviews, and documented qualitative data as data collection techniques. The data were analyzed thematically based on structural-functional theory, social system theory, Hindu cosmology, and theories of symbols and rituals. The findings indicate that Pura Braban functions not only as a place of worship and spiritual purification but also as a social institution that facilitates the integration of krama subak abian, the transmission of cultural values, and norm-based social control grounded in religion and customary law. The spatial structure of the temple reflects Balinese Hindu cosmology through the concepts of tri mandala and triloka, while ritual practices serve as a medium for internalizing religious values and social solidarity. From an anthropological perspective, Pura Braban represents a cultural arena in which religion is lived as a dynamic, contextual, and sustainable system of meaning. This study underscores the importance of preserving temples and Ilikita Purana as part of sustaining religious, social, and cultural continuity in Bongkasa Village